Answer :

Given: sin2θ cos2θ (1 + tan2θ) (1 + cot2θ) = λ

To find: λ


We know that 1 + tan2 θ = sec2 θ


And 1 + cot2 θ = cosec2 θ


sin2θ cos2θ (1 + tan2θ) (1 + cot2θ)


= sin2 θ cos2 θ sec2 θ cosec2 θ


Now,



And



sin2 θ cos2 θ (1 + tan2 θ) (1 + cot2 θ)


= sin2 θ cos2 θ sec2 θ cosec2 θ



λ = 1


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Trigonometric IdentitiesTrigonometric IdentitiesTrigonometric Identities39 mins
Trigonometric Identities-IITrigonometric Identities-IITrigonometric Identities-II43 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses